Comparative Analysis Tumor Detection and Segmentation Exploitation Watershed Technique - Josephine, S; Murugan, S (International Journal of Computer Sciences and Engineering, 2025)
Five totally different threshold segmentation primarily based approaches are reviewed and compared up here to extract the growth from set of brain pictures. This analysis focuses on the analysis of image segmentation ways, a comparison of 5 semi-automated ways are undertaken for evaluating their relative performance within the segmentation of growth. Consequently, results square measure compared on the idea of quantitative and analysis of individual ways. The aim of this study was to analytically determine the ways, most fitted for application for a selected genre of issues. The results show that of the region growing segmentation performed on top of rest in most cases